2021
DOI: 10.2196/25652
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Tools for Managing Noncommunicable Diseases During and After the COVID-19 Pandemic: Perspectives of Patients and Caregivers

Abstract: Background A reduction in the number of face-to-face medical examinations conducted for patients with noncommunicable diseases (NCDs) during the first wave of the COVID-19 pandemic has led to health care professionals quickly adopting different strategies to communicate with and monitor their patients. Such strategies include the increased use of digital health tools. However, patient preferences, privacy concerns, a lack of regulations, overregulation, and insufficient evidence on the efficacy of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 27 publications
1
31
0
1
Order By: Relevance
“…For example, recruiting frail participants for inperson visits during a lockdown or "shelter in place" advisory in the surrounding community 24,25 and conducting virtual information and consent discussions where technology (eg, tablet devices) may be unfamiliar or present barriers due to sensory impairments are all very real considerations. 26 Even so, when means of working around these barriers are developed, the payoff will be much better population representativeness. Overcoming these sorts of barriers is part of the routine skill set of geriatricians in clinical settings (even pre-COVID).…”
Section: Trial Recruitmentmentioning
confidence: 99%
“…For example, recruiting frail participants for inperson visits during a lockdown or "shelter in place" advisory in the surrounding community 24,25 and conducting virtual information and consent discussions where technology (eg, tablet devices) may be unfamiliar or present barriers due to sensory impairments are all very real considerations. 26 Even so, when means of working around these barriers are developed, the payoff will be much better population representativeness. Overcoming these sorts of barriers is part of the routine skill set of geriatricians in clinical settings (even pre-COVID).…”
Section: Trial Recruitmentmentioning
confidence: 99%
“…These large-scale disasters occurring simultaneously created unprecedented, long-term health care challenges. As cities and states across the United States reached peak COVID-19 cases and hospitalizations, health care systems relied on public health guidance to limit in-person patient appointments and services [ 61 , 62 ]. There has been a large increase in the adoption of the patient portal in terms of general use and depth of use [ 63 ], including substantial dependence on the use of telehealth platforms and portal messaging for care management of patients [ 61 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…As cities and states across the United States reached peak COVID-19 cases and hospitalizations, health care systems relied on public health guidance to limit in-person patient appointments and services [ 61 , 62 ]. There has been a large increase in the adoption of the patient portal in terms of general use and depth of use [ 63 ], including substantial dependence on the use of telehealth platforms and portal messaging for care management of patients [ 61 , 64 ]. Medical information technology allowed health care providers a key method with which to continue accommodating patient services safely while reserving hospital capacity for the most critically ill.…”
Section: Discussionmentioning
confidence: 99%
“…The emphasis on technology-based interventions for cancer caregivers has become particularly pronounced amid the COVID-19 pandemic, a global health crisis that has effectively crippled many, if not all, of the traditional health care services available to patients and caregivers [21][22][23]. During the pandemic, many cancer caregivers have found much-needed solace and support in technology-based health care services, ranging from online support groups to videoconferencing with patients or health care professionals [24][25][26]. It is important to note that there is a growing body of research investigating the benefits of technology-based health solutions [24][25][26][27][28][29].…”
Section: The Critical Role Of Technology-based Interventionsmentioning
confidence: 99%
“…During the pandemic, many cancer caregivers have found much-needed solace and support in technology-based health care services, ranging from online support groups to videoconferencing with patients or health care professionals [24][25][26]. It is important to note that there is a growing body of research investigating the benefits of technology-based health solutions [24][25][26][27][28][29]. For instance, a systematic review revealed that caregivers significantly improved their cancer knowledge and communication outcomes after receiving technology-based interventions [27].…”
Section: The Critical Role Of Technology-based Interventionsmentioning
confidence: 99%